Exempting the practice of sports from the circle of criminalization - herizi, abdelhadi (sports creativity, 2025)
In our modern age, sports play a significant role in capturing public attention, with news about them being a daily topic of conversation. This is evidenced by the public's eagerness to check the sports section of daily newspapers. Given the diverse perspectives of the public on sports—some focusing on its physical health benefits, others on its financial potential, still others on the competitive aspect, and some on its recreational value—and the professional aspects (especially among experts) of developing sports within the country, the field of sports is undoubtedly subject to regulation and direction. Sports are among the important subjects addressed by law due to their potential consequences, which can even lead to loss of life. This research examines the most important legal provisions concerning sports injuries, which frequently occur among athletes, analyzing them through a legal study and the relevant provisions of contemporary positive law. With this surge in interest in sports, the need for legal research addressing the issues related to this field and clarifying the legal position on them becomes evident. This study has identified the most important issues and legal regulations pertaining to the sports sector, presenting the opinions of legal experts, clarifying their evidence, and discussing it whenever possible, ultimately arriving at several relevant conclusions.